Makanan Pendamping Asi, Ketahanan Pangan, dan Status Gizi Balita di Bekasi - Selvi Purnama Dewi; Adhila Fayasari (Universitas Islam Negeri Walisongo Semarang, 2020)
AbstractThis study aims to analyze the relationship between complementary feeding, food security, and nutritional status (Weight-for-age (WAZ)) of children aged 6-59 months in Bekasi. This study used cross sectional design of 135 pairs of mothers and children aged 6-59 months in the Jatiluhur Primary Health Center, Bekasi City. Provision of complementary feeding and food diversity were collected using questionnaire. Food Security was collected using (Household Food Insecurity Access Scale- HFIAS) questionnaire. Anthropometic data was collected using weighing scale and was converted into z-score using WHO-Anthroplus software. Data were analysed by chi-square/Fischer exact test with 5% significant p value. The result showed that 86 (63.7%) children were underweight (z-score -1 SD). There was a significant relation between timing of introduction complementary feeding and nutritionaatus (p = 0.031). On the other hand, there was no significant relation between food security and food diversity with nutritional status. This study showed that that the timing of introduction complementary feeding is significantly related to the nutritional status of children in Bekasi. AbstrakPenelitian ini bertujuan untuk menganalisis hubungan pemberian makanan pendamping ASI dan ketahanan pangan dengan status gizi balita (BB/U) usia 6-59 bulan di puskesmas wilayah Kota Bekasi. Penelitian ini menggunakan desain cross sectional pada 135 ibu dan balita usia 6-59 bulan di wilayah Puskemas Jatiluhur, Bekasi. Data karakteristik, keragaman pangan dan riwayat pemberian MP-ASI diukur menggunakan kuesioner, ketahanan Pangan diukur dengan kuesioner Household Food Insecurity Access Scale- (HFIAS). Data status gizi didapatkan dengan pengukuran berat badan kemudian diolah menggunakan software WHO-Antrhoplus. Analisis statistik yang digunakan adalah uji chi-square/fischer exact dengan tingkat kesalahan 5%. Sebanyak 86 balita (63,7%) memiliki status gizi kurang (z-score -1 SD). Terdapat hubungan antara waktu pemberian MP-ASI dengan status gizi balita BB/U ( p = 0,031). Tidak terdapat hubungan ketahanan pangan, keragaman pangan, frekuensi dan jenis pemberian MP-ASI dengan status gizi balita BB/U (p=0,443). Berdasarkan penelitian yang dilakukan, hanya waktu pemberian MP-ASI yang terkait dengan status gizi balit di bekasi.